The potency and problems of natural tourism object Dolok Simago-Mago Sipirok in South Tapanuli Regency / Sri Yanti Hasibuan - SRI Yanti Hasibuan; MARSONO (Polytechnic PPKP Yogyakarta, 2005)
xvi, 28 lembar ; 29,5 cm.